Using action learning to support mobile pedagogies: the role of facilitation. Issue 4 (7th August 2020) - Maher, Damian; Schuck, Sandy
ABSTRACT: The rate of change in the use of digital technologies in schools means that professional learning regarding technology-enhanced learning is constantly required for school teachers. The focus of this article is on how an action learning (AL) approach supported the professional learning of teachers regarding adoption of mobile technologies in their teaching. In particular, the article investigates the role of facilitation in the action learning process and explores an AL process implemented at two schools, one a primary school and the other a secondary school. Drawing on qualitative methodology, a multi-site case study using observations, field notes and interviews was implemented to investigate the effectiveness of the AL approach. It was found that different kinds of facilitation were central to the success of the process, and that facilitation impacted on teacher agency. The article concludes with recommendations for action learning projects.